2019
DOI: 10.1051/matecconf/201930402020
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Analysis of Model–Support Interference in Low-Speed Wind-Tunnel Testing of Fuselage-Boundary-Layer Ingestion

Abstract: Junction flow caused by the aerodynamic interaction between a wind-tunnel model and the support structure can largely influence the flowfield and hence the experimental results. This paper discusses a combined numerical and experimental study which was carried out to mitigate the model–support interference in a wind-tunnel test setup for the study of fuselage boundary-layer ingestion. The setup featured an axisymmetric fuselage mounted through a support beam, covered by a wing-shaped fairing. The junction flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The bottom fairing did not have any structural function and was employed to reduce the effects of the fairings on the flowfield around the fuselage aft section. More details of the fairing design were presented in a previous related work [28].…”
Section: Fairing Configurationmentioning
confidence: 99%
“…The bottom fairing did not have any structural function and was employed to reduce the effects of the fairings on the flowfield around the fuselage aft section. More details of the fairing design were presented in a previous related work [28].…”
Section: Fairing Configurationmentioning
confidence: 99%
“…The findings underscored the substantial impact of FPR on the required shaft power, revealing that a 10% reduction in FPR resulted in a remarkable 36% reduction in shaft power. On the other hand, a series of experimental studies confirmed preliminary simulations of this PFC aircraft [215][216][217]. Particle image velocimetry techniques were employed to investigate the main aerodynamic phenomena, and the power balance method was employed to evaluate the aerodynamic and propulsive forces.…”
Section: Propulsive Fuselage Conceptsmentioning
confidence: 89%
“…Additionally, aerodynamic forces analysis based on power balance method [21] was conducted. The simplified PFC model geometry was based on the study performed by Della Corte et al [137] that focused on the optimization of the PFC fuselage and its structure support within the wind tunnel facility. The BLI propulsor was sized to ensure aerodynamic similarity with the CENTRELINE full-scale fan developed by Castillo Pardo and Hall [23].…”
Section: Centreline Conceptmentioning
confidence: 99%